Cell-free DNA in non-small cell lung cancer - Gedvilaitė, Vaida; Schveigert, Diana; Cicėnas, Saulius (Acta medica Lituanica, 2017)
Lung cancer is the leading cause of cancer-associated deaths worldwide. Surgery is the standard treatment for early-stage non-small cell lung cancer (NSCLC). Advances in the knowledge of the biology of non-small cell lung cancer have revealed molecular information used for systemic cancer therapy targeting metastatic disease, with an important impact on patients’ overall survival (OS) and quality of life. However, a biopsy of overt metastases is an invasive procedure limited to certain locations and not easily acceptable in the clinic. The analysis of peripheral blood samples of cancer patients represents a new source of cancer-derived material, known as liquid biopsy, and its components (circulating tumour cells (CTCS), circulating free DNA (cfDNA), exosomes, and tumour-educated platelets (TEP)) can be obtained from almost any body fluids. These components have shown to reflect characteristics of the status of both the primary and metastatic diseases, helping the clinicians to move towards a personalized medicine (1). This review focuses on the liquid biopsy component – circulating free DNA, its benefit for non-invasive screening, early diagnosis, prognosis, response to treatment, and real time monitoring of the disease in non-small cell lung cancer patients.